Temperature dependence of the zero-dispersion wavelength of dispersion-shifted fiber - Kim, SH; Kim, DH; Jo, JC; Cho, KM (JAPAN J APPLIED PHYSICS, 1998)
We measured the temperature dependence of the zero-dispersion wavelength of dispersion-shifted fibers using a four-wave mixing process in the range of 22 degrees C-59 degrees C. From the experimental results, we found that the zero-dispersion wavelength increases linearly as the temperature around dispersion-shifted fiber(DSF) increase, and its slope is 0.032 nm/degrees C.
Keywords: AMPLIFIER